Dual-Band Microstrip Antenna Design for 2.4 GHz and 5.3 GHz WiFi Networks - Muhammad Zainul Arifin; Syah Alam (International Journal Software Engineering and Computer Science (IJSECS), 2026)
This study reports the design and simulation of a dual-band rectangular patch microstrip antenna intended for Wi-Fi applications at 2.4 GHz and 5.3 GHz. Initial patch dimensions were derived analytically at 2.4 GHz, then refined through an iterative optimization process involving the progressive insertion of vertical slots on the radiating patch. Three iterations were performed, each modifying slot length and width to shift the second resonant frequency toward the 5.3 GHz target while preserving the first resonance at 2.4 GHz. The finalized design resonated at approximately 2.49 GHz and 5.3 GHz, with return loss values of −16.11 dB and −15.5 dB, respectively — both satisfying the −10 dB threshold commonly adopted as the minimum criterion for acceptable antenna matching. VSWR values of 2.945 at 2.493 GHz and 2.613 at 5.3 GHz were recorded; these remain above the ideal upper bound of 2, indicating that impedance matching between the antenna and the feed line has not been fully resolved. Measured bandwidths were 143 MHz at 2.498 GHz and 2.8 MHz at 5.3 GHz, with the notably narrow bandwidth at the higher frequency representing a practical limitation that warrants further attention. Gain at 2.498 GHz reached 6.01 dBi, while the value at 5.2 GHz dropped to −4.369 dBi, suggesting that the slot geometry, though effective for frequency tuning, introduced radiation efficiency losses at the upper band. Taken together, the results confirm that vertical slot insertion is a viable technique for generating dual-band resonance in a rectangular patch microstrip antenna; the approach, however, requires additional refinement — particularly in impedance matching and upper-band gain recovery — before the design can be considered fully deployment-ready.